Pengembangan Wawasan Multikultural Melalui Model Sejarawan Kecil Pecinan Dan Klenteng Sam Poo Kong Semarang - Soeharso R. (Historia Pedagogia, 2026)
This study aims to analyze the needs and develop a multicultural based “little historians” learning model by utilizing Semarang’s Chinatown and the Sam Poo Kong Temple as sources for local history learning. The Study was motivated by student’s low interest history learning, limited learning resources, and the suboptimal nature of learning models capable of developing student’s historical thinking skills. The study employs a Research and Development (R&D) method adapted from Newby’s model through three stages: need analysis, model development, and dissemination of research findings. The research subjects include high school history teachers in Semarang city who are members of the History Teacher’s Working Group (MGMP Sejarah). Data collection was conducted through observation, interviews, FGD, document analysis, and expert validation questionnaires. The result indicate that the ‘little historian’ learning model based on local history is capable of providing more engaging, contextual and students centered learning experiences. This model also effective to developing students historical thinking, historical analysis and interpretation and historical research capabilities. Expert validation result showed a feasibility rate of 95,14% categorizing the model as highly suitable for use in history education based on local and multicultural history.